Superconductivity-induced magnetization depletion in a ferromagnet through an insulator in a ferromagnet–insulator–superconductor hybrid oxide heterostructure. Issue 19 (28th April 2016) - Prajapat, C. L.; Singh, Surendra; Paul, Amitesh; Bhattacharya, D.; Singh, M. R.; Mattauch, S.; Ravikumar, G.; Basu, S.
Abstract : Magnetization depletion in La2/3 Ca1/3 MnO3 (LCMO) layers as a result of tunneling of Cooper pairs across an insulator SrTiO3 (STO) in LCMO/STO/YBa2 Cu3 O7− δ (YBCO) heterostructures. Abstract : Coupling between superconducting and ferromagnetic states in hybrid oxide heterostructures is presently a topic of intense research. Such a coupling is due to the leakage of the Cooper pairs into the ferromagnet. However, tunneling of the Cooper pairs though an insulator was never considered plausible. Using depth sensitive polarized neutron reflectivity we demonstrate the coupling between superconductor and magnetic layers in epitaxial La2/3 Ca1/3 MnO3 (LCMO)/SrTiO3 /YBa2 Cu3 O7− δ (YBCO) hybrid heterostructures, with SrTiO3 as an intervening oxide insulator layer between the ferromagnet and the superconductor. Measurements above and below the superconducting transition temperature ( T SC ) of YBCO demonstrate a large modulation of magnetization in the ferromagnetic layer below the T SC of YBCO in these heterostructures. This work highlights a unique tunneling phenomenon between the epitaxial layers of an oxide superconductor (YBCO) and a magnetic layer (LCMO) through an insulating layer. Our work would inspire further investigations on the fundamental aspect of a long range order of the triplet spin-pairing in hybrid structures.